Antiepileptic Drug Withdrawal in Dogs with Epilepsy - Gesell, Felix Kaspar; Hoppe, Sonja; Löscher, Wolfgang; Tipold, Andrea (Frontiers in Veterinary Science, 2015)
Epilepsy is one of the most common neurological disorders in dogs and is treated by chronic administration of antiepileptic drugs (AEDs). In humans with epilepsy, it is common clinical practice to consider drug withdrawal after a patient has been in remission (seizure free) for three or more years, but withdrawal is associated with the risk of relapse. In the present study, the consequences of AED withdrawal were studied in dogs with epilepsy. Therefore, 200 owners of dogs with idiopathic or presumed idiopathic epilepsy were contacted by telephone interview, 138 cases could be enrolled. In 11 cases the therapy had been stopped after the dogs had become seizure free for a median time of 1 year. Reasons for AED withdrawal were appearance or fear of adverse side effects, financial aspects and the idea that the medication could be unnecessary. Following AED withdrawal, 4 of these dogs remained seizure free, 7 dogs suffered from seizure recurrence, of which only 3 dogs could regain seizure freedom after resuming AED therapy. Due to the restricted case number, an exact percentage of dogs with seizure recurrence after AED withdrawal cannot be given. However, the present study gives a hint that similar numbers as in human patients are found, and the data can help owners of epileptic dogs and the responsible clinician to decide when and why to stop antiepileptic medication.